Vojta Approach Affects Neck Stability and Static Balance in Sitting Position of Children With Hypotonia - Sun-Young Ha (Korean Continence Society, 2021)
Purpose In this study, the effect of the Vojta approach on neck stability and static balance in children with hypotonia was studied. Methods Seventeen children with hypotonia were randomly divided into the Vojta approach group (n=9) and the general physical therapy group (n=8). Each group was applied intervention for 30 minutes per session, 3 times a week, for a total of 4 weeks. Ultrasonography was used to measure deep neck flexor muscle thickness, craniovertebral angle (CVA) to measure neck alignment along the spine segment, and Balancia software program to measure static balance. Results In the Vojta approach group, the deep neck flexor muscle thickness was significantly increased (P<0.05), and the CVA was significantly improved (P<0.05). In addition, path area among static balance was significantly improved (P<0.05). Conclusions The Vojta approach can be suggested as an effective intervention method for improving neck stability and static balance in children with hypotonia.